P627Systemic toll-like receptor 9 activation increases mortality in SERCA2a KO mediated diastolic heart failure. (15th July 2014) - Holmen, YD; Sjaastad, I; Yndestad, A; Ranheim, T; Alfsnes, K; Aronsen, JM; Gullestad, L; Aukrust, P; Christensen, G; Vinge, LE
Abstract: Purpose: Systemic inflammation in established HF is clinically relevant as many HF patients have concomitant chronic inflammatory conditions. Repetitive activation of Toll-like receptor 9 (TLR9) induces chronic inflammation. We used a pharmacological protocol to induce systemic, chronic inflammation in murine cardiomyopathy induced by cardiomyocyte specific deletion of SERCA2a. Methods: Cardiac expression of SERCA2a was deleted in 10 week old male αMHC-MerCreMer Serca2a flox/flox mice by one intraperitoneal injection of Tamoxifen, resulting in a lethal diastolic HF phenotype after 7 weeks. 4 weeks after conditional knock out (KO), mice were randomized to TLR9 agonist (CpG-B;50 mg i.p.) or PBS every 3 days. Echocardiography was performed 8 weeks after induction of HF, followed by euthanization and analyses of tissue and blood. The groups were followed for 12 weeks, registering death and morbidity (by pre-specified criteria). Non-HF control groups treated with CpG-B or PBS served as controls. Results: TLR9 stimulated mice showed alterations in levels of leukocytes, erythrocytes and platelets as measured by flow cytometry and peripheral blood count, as well as pulmonary inflammation and hypersplenism (histology). The alterations were not found in controls. Echocardiographic analyses revealed aggravation in diastolic parameters in HF mice treated with CpG B. The latter group had reduced life expectancy compared with HF controls (median 59.5 and 68.5 days respectively, p=0.003). Non-HF, CpG B treated mice did not die or display signs of disease within the observation period. Conclusions: Chronic inflammation promoted by continuous TLR9 stimulation worsens diastolic HF caused by SERCA2a deletion. This study may provide insight into the consequences of chronic inflammatory conditions on HF development.